Managing Technological Change in Libraries - Singh, Prem (Journal of Information and Knowledge, 1991)
Discusses the various faces of information technology that are emorging. Identifies their impact on library and its services. Discusses the strategies that are to be followed for adopting information technology in a phased mannner.